Interdisciplinary, inter-institutional and international group “NanoSilver”: Application of silver nanoparticles Argovit in biomedicine and veterinary; International Multidisciplinary Joint Meeting 2013 - Bogdanchikova N.; C. A. Almonaci H.; A. Salinas R.; M. Maldonado V.; J. H. Almanza Reyna V.; I. Plascencia L.; A. Pena J.; Pestryakov A. N. Aleksey Nikolaevich; Burmistrov V.; L. Garcia M.; R. Vazquez M.; M. E. Arellano G.; et al. (2013, 2013)
В фонде НТБ ТПУ отсутствует